S-band erbium-doped fiber ring laser using a fiber Bragg grating - Ahmad, H.; Saat, N. K.; Harun, S. W. (2005)
A short wavelength band erbium-doped fiber laser (S-band EDFL) is demonstrated utilizing a fiber Bragg grating (FBC) in unidirectional ring configuration. The amplification in S-band is achieved using an erbium-doped fiber wit depressed cladding, which suppressed gains at longer wavelength. The laser operates at 1500 nm, which coincides with the FBG wavelength. The optimum EDFL operation is obtained by routing only 10% of the laser output into the cavity. The laser has an output power of 7.8 dBm, more than 60 dB of peak to floor separation and 3 dB bandwidth of less than 0.08 nm. This fiber laser provides an inexpensive source for tunable output in the wavelength range from 1480 to 1520 nm.